Induction of atrial fibrillation with rapid high voltage ventricular pacing for ventricular fibrillation conversion testing - Schuchert, A (2000)
OBJECTIVE—To assess whether rapid high voltage ventricular pacing can also induce atrial fibrillation, and whether the induction of atrial fibrillation during ventricular fibrillation conversion testing is related to the patient's heart disease. DESIGN—Prospective study of 50 patients who received the dual chamber implantable cardioverter-defibrillator (ICD) Ventak AV II DR (Guidant) as a first implant. This device can record atrial activity even during a ventricular fibrillation episode and can induce atrial fibrillation by rapid atrial bursts. MAIN OUTCOME MEASURES—Frequency of atrial fibrillation after induction of ventricular fibrillation; clinical characteristics of patients with and without induced atrial fibrillation; frequency of atrial fibrillation induced by rapid atrial bursts during predischarge testing. RESULTS—Atrial fibrillation was observed in 40 of the 217 ventricular fibrillation episodes (18%) that could be detected immediately after delivery of high voltage pacing. The biphasic ICD shock for termination of ventricular fibrillation also terminated the atrial fibrillation in all cases. The 40 episodes of simultaneous atrial and ventricular fibrillation occurred in 18 patients (36%). The distribution of the clinical characteristics of the patients and the inducibility of atrial fibrillation during predischarge testing were similar in those with and without induced atrial fibrillation. CONCLUSIONS—Rapid high voltage ventricular pacing frequently induces atrial fibrillation, which was terminated by the subsequent biphasic ICD shock. The induction of atrial fibrillation seems to be a non-specific phenomenon, unrelated to the clinical status of the patient.   Keywords: dual chamber implantable cardioverter-defibrillator; atrial fibrillation induction; ventricular fibrillation conversion test; high voltage ventricular pacing; atrial burst pacing